Swimming performance and ecomorphology of the Iberian barbel Luciobarbus bocagei (Steindachner, 1864) on permanent and temporary rivers. - Almeida, Pedro R. (2015)
Spatial variability in streamflow characteristics is responsible for a large range of habitat variations to which fish are adapted through life-cycle strategies and morphological adaptations. In this study, we compared the swimming performance and related morphology of two Iberian barbel populations from permanent and temporary rivers. The permanent river was characterised by its Atlantic influence with higher water availability and a more unstable and turbulent environment, contrasting with the lower discharge setting observed in the southern Mediterranean ecosystem during most of the hydrological year. Barbels from the permanent river exhibited a higher critical swimming speed (Ucrit) associated with a more fusiform body shape, narrower head and caudal peduncle, lower body condition and longer and higher pectoral and dorsal fins, when compared with the population from the temporary watercourse. These results reflect a morphological response in a way to reduce hydrodynamic resistance and energy expenditure during locomotion that we hypothesise here to be related with the different hydrological regimes of the studied systems.